2014
DOI: 10.1073/pnas.1319683111
|View full text |Cite
|
Sign up to set email alerts
|

Fringe-mediated extension of O -linked fucose in the ligand-binding region of Notch1 increases binding to mammalian Notch ligands

Abstract: The Notch signaling pathway is essential for many aspects of development, cell fate determination, and tissue homeostasis. Notch signaling can be modulated by posttranslational modifications to the Notch receptor, which are known to alter both ligand binding and receptor activation. We have modified the ligand-binding region (EGF domains 11-13) of human Notch1 (hN1) with O-fucose and O-glucose glycans and shown by flow cytometry and surface plasmon resonance that the Fringe-catalyzed addition of GlcNAc to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
127
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(149 citation statements)
references
References 49 publications
22
127
0
Order By: Relevance
“…Significantly, addition of the O-glucose trisaccharide did not alter the conformation of the EGF repeat. We had previously shown that addition of O-fucose monosaccharide or disaccharide to EGF12 of Notch1 also does not induce conformational change of the EGF repeat, but similar to what we observed here, the O-fucose glycan has multiple interactions with underlying amino acids (40). Similar results have been reported by other investigators (37,39).…”
Section: O-glycans Modulate Egf Protein Stabilitysupporting
confidence: 92%
See 1 more Smart Citation
“…Significantly, addition of the O-glucose trisaccharide did not alter the conformation of the EGF repeat. We had previously shown that addition of O-fucose monosaccharide or disaccharide to EGF12 of Notch1 also does not induce conformational change of the EGF repeat, but similar to what we observed here, the O-fucose glycan has multiple interactions with underlying amino acids (40). Similar results have been reported by other investigators (37,39).…”
Section: O-glycans Modulate Egf Protein Stabilitysupporting
confidence: 92%
“…We further compared the above-described structures with the structure of EGF12 either unmodified or modified with an O-fucose monosaccharide or an O-fucose disaccharide (Fig. 5, A and E-G) (40), and we found that O-fucose glycans are on the opposite side of the protein from where the O-glucose glycans attach. This result supports our cell biological and biochemical observation that the effects of O-fucose and O-glucose on EGF repeats are independent and therefore additive.…”
Section: Structural Analysis Of Hfa9 Egf Repeat Modified With Oglucosmentioning
confidence: 99%
“…In our mass spectral analyses, we were particularly interested in determining which O-fucose sites were modified by Fringe because those sites should play important roles in the effects Fringe has on Notch. Recent structural studies on the ligand binding domain of mammalian Notch1 show that the O-fucose glycans on EGF12 directly interact with ligands upon binding (22,50). From the EIC analysis, we observed that Fringe elongates some sites more efficiently than others.…”
Section: Xxxx(s/t)cmentioning
confidence: 73%
“…Loss of Ofut1/Pofut1 in flies or mice results in Notch-null phenotypes, indicating that O-fucosylation is essential for Notch function (18 -20). The ␤3GlcNAc-transferases of the Fringe family can extend O-fucose in flies and mammals (21) and most notably play important roles in modulating Notch-ligand binding (22)(23)(24)(25). In mammals, the GlcNAc␤1-3Fuc-O-Ser/Thr disaccharide can be further elongated to a tetrasaccharide: Sia␣2-6Gal␤1-4GlcNAc␤1-3Fuc-O-Ser/Thr (26).…”
mentioning
confidence: 99%
“…The analysis by Luca and colleagues also revealed how the addition of O-fucose and O-glucose to threonine and serine residues on Notch1 functionalizes the receptor by making specific and essential contacts with residues on DLL4. Collaborative work from Robert Haltiwanger (Stony Brook University, USA) and Handford further showed how Fringemediated addition of GlcNAc to O-fucose increases binding of Notch1 to Notch ligands (Taylor et al, 2014). These observations illustrate how post-translational modifications of ligand-binding sites on Notch proteins that are regulated by specific biosynthetic pathways provide a strategy for regulating Notch function during development.…”
Section: Notch-ligand Interactions and The Mechanics Of Notch Activationmentioning
confidence: 90%